Effect of Ratio of Papaya and Starfruit Pulp with Carrageenan Concentration on the Quality of Sheet Jam - Daniel Sitanggang; Herla Rusmarilin; Linda Masniary Lubis (Universitas Sumatera Utara, 2015)
Papaya and starfruit production in Indonesia is very abundant, but their processing is still very minimal, therefore the diversification of their processing is needed to increase. This study was conducted to determine the effect of ratio of papaya and starfruit pulp with carrageenan concentration on the quality of jam sheet. This study used a completely randomized design with two factors namely ratio of papaya and starfruit pulp (B): 80%:20%, 60%:40%, 40%:60%, and 20%:80%, and carrageenan concentration (K): 2,5%, 3,5%, 4,5% and 5,5%. The parameters analyzed were moisture content, total acid, vitamin C, total dissolved solids, color and texture scores as well as organoleptic values of color, aroma, taste and texture. The results showed that the ratio of papaya and starfruit pulp had highly significant effect on water content, total acid, vitamin C, total dissolved solids, texture scores as well as organoleptic value of taste and texture. Carrageenan concentration had highly significant effect on water content, total dissolved solids, vitamin C, color scores, texture scores as well as organoleptic of color, taste and texture. Interaction of the two factors had highly significant effect on water content and test scores texture. The ratio of papaya and starfruit pulp of 80%:20% with concentration of 4,5% carrageenan gave the best quality characteristics of the sheet jam and still acceptable for consumption. Keywords: Carrageenan, papaya, sheet jam, starfruit.